Myocardial scarring and recurrence of ventricular arrhythmia in patients surviving a ventricular fibrillation out of hospital cardiac arrest. (3rd October 2022) - Thomsen, A F; Winkel, B G; Jons, C; Bertelsen, L; Bhardwaj, P; Stampe, N K; Kober, L; Engstrom, T; Vejlstrup, N G; Jacobsen, P K
Abstract: Introduction: Prediction of ventricular arrhythmia recurrence in survivors of ventricular fibrillation out of hospital cardiac arrest (VF-OHCA) is important, but currently difficult. Risk of recurrence may be related to presence of myocardial scarring and dedicated late gadolinium enhancement cardiac magnetic resonance (LGE-CMR) software allows for characterization of left ventricular scarring, including differentiation between core, border zone (BZ) and BZ channels that represent potential electrical circuits of slow conductivity responsible for ventricular arrhythmic events. Purpose: Our study aims to characterize myocardial scarring as defined by LGE-CMR in survivors of a VF-OCHA and investigate its potential role for the risk of new ventricular arrhythmia. Methods: Between 2018 and 2021, a total of 130 VF-OHCA patients had CMR, of which we included 28 patients with LGE-CMR before ICD implantation for secondary prevention. A total of 15 (54%) patients had signs of acute or chronic ischemic heart disease (IHD); and 13 (46%) patients had arrhythmogenic cardiomyopathy (ACM). Scar tissue including core, BZ and BZ channels were automatically detected by specialized investigational software. To differentiate BZ from healthy tissue and BZ from core, thresholds of 40% ± 5% and 60% ± 5% of the maximum signal intensity were applied. A BZ channel in the LGE-CMR reconstruction was defined as a continuous corridor of BZ between 2 core areas or between a core area and a valve annulus (Figure 1A+B). Results: The median age was 56 years; 86% were men and the median left ventricular ejection fraction was 50±11%. A total of 16 (57%) patients had an inferior scar on LGE-CMR, and 8 (29%) patients with IHD were incompletely revascularized. After a median follow-up of 98 days, 9 (32%) patients (6/9 with IHD, including 5/6 incompletely revascularized; 3/9 with ACM) had recurrence of ventricular arrhythmia (6/9 monomorphic ventricular tachycardia (VT)). A significantly higher number of patients with BZ channels had recurrence of ventricular arrhythmia compared with patients without BZ channels (7/11 vs. 2/17; P=0.01) (Figure 2). The number of BZ channels (3±1 vs. 2±1; P=0.13); scar mass (21±8g vs. 14±11g; P=0.21); core mass (7±4g vs. 4±5g; P=0.14); and BZ mass (11±5g vs. 9±7g; P=0.42) were insignificantly higher in patients with recurrent ventricular arrhythmia compared with patients without. Conclusion: Borderzone channels analyzed by LGE-CMR were associated with subsequent recurrence of ventricular arrhythmia in patients with out of hospital cardiac arrest caused by ventricular fibrillation. Funding Acknowledgement: Type of funding sources: None.